General Awareness about Epilepsy in a Cohort of Female and Male Students: A Statistical Comparison - Jaseja, Harinder; Verma, Jai Prakash; Mehndiratta, Man Mohan; Govila, Anand Kumar; Tiwari, Jyoti; Gupta, Sandeep; Grover, Vijmendra Kumar; Kumari, Priti; Parashar, Gajendra; Bansal, Neeraj (International Journal of Epilepsy, 2018)
Background and Objective A survey on general awareness toward epilepsy was conducted on a cohort of female and male medical and paramedical students that represent a model educated section of the society. It is, therefore, imperative that this section of the society acquires correct knowledge about epilepsy.Materials and Methods The subjects were undergraduate students from medical and paramedical institutes in Gwalior region who were gathered to celebrate the National Epilepsy Day on November 17, 2016. A self-administered questionnaire of 50 questions on general awareness about epilepsy was completed at the very beginning before the celebrations. The results were subjected to various statistical analyses.Results A total of 251 respondents (149 females and 102 males) in the age group of 17 to 31 years participated in the survey. All the respondents had heard about epilepsy. One-hundred fifty-eight participants were from medical and dental institutes, whereas 93 participants were from paramedical institutes. In general, the female participants exhibited significantly greater general knowledge about epilepsy in comparison to the male respondents.Conclusion The results indicate a favorable degree of awareness about epilepsy. A definite knowledge gap was observed between the medical and paramedical students. However, the awareness still needs to be enhanced even among students pursuing medical and paramedical courses through various programs apart from their academic curriculum, as a certain degree of misconceptions and superstitious beliefs associated with epilepsy continues to prevail even in this educated section of the society.
Keywords: patients with epilepsy; misconceptions; medical students; paramedical students; National Epilepsy Day